Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.inteco.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The exchange rate, asymmetric shocks and asymmetric distributions

Abstract: The exchange rate, asymmetric shocks and asymmetric distributions ECB Working Paper, No. 1801 Provided in Cooperation with: European Central Bank (ECB)Suggested Citation: Demian, Calin-Vlad; di Mauro, Filippo (2015) : The exchange rate, asymmetric shocks and asymmetric distributions, ECB Working Paper, No. 1801, ISBN 978-92-899-1614 Non-technical SummaryThe link between exchange rates and international trade has been the subject of a broad body of literature without a clear consensus on the size of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(25 reference statements)
3
11
0
Order By: Relevance
“…REERs by firm-level productivity quartile on CompNet data for 11 EU countries in the period 2001-2011. Comparable results are also found in Demian and di Mauro (2015).…”
Section: Stylized Fact #6: the Elasticity Of Exports To Changes In Thsupporting
confidence: 80%
“…REERs by firm-level productivity quartile on CompNet data for 11 EU countries in the period 2001-2011. Comparable results are also found in Demian and di Mauro (2015).…”
Section: Stylized Fact #6: the Elasticity Of Exports To Changes In Thsupporting
confidence: 80%
“…Hence, instead, the firm may reduce the quantity of exports. In their results regarding asymmetric effects, Demian and di Mauro () show that a 10% real appreciation reduces the value of exports by 10%. Real depreciation has no noticeable impact, with either an insignificant coefficient or a coefficient of size zero.…”
Section: The Literaturementioning
confidence: 97%
“…They focus on the response of CPI prices in the G7 countries over the period 1970–2009. Others have shown that export shares may respond more strongly to real exchange rate appreciations than depreciations (Cheung & Sengupta, ; Demian & di Mauro, ) or that firm‐level output may respond differently to real appreciations than to real depreciations (Dhasmana, ). The trade balance is also shown to respond in an asymmetric manner to exchange rate changes when Bahmani‐Oskooee and Fariditavana () estimated the U.S. bilateral trade balance models with its six largest partners in assessing the J‐curve effect.…”
Section: The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Dhasmana (2015) stresses the importance of industry concentration, access to domestic finance, and foreign ownership. Demian and di Mauro (2018) propose that it responds to quantity rigidities, impeding firms from selling as much as demanded after depreciations, and price rigidities restraining exporters to lower prices enough after appreciations. Javed et al (2016) state that real depreciations in Pakistan tend to fall short of correcting an already overvalued currency, although without formally testing the underlying drivers of the claim.…”
Section: Introductionmentioning
confidence: 99%